EFEKTIFITAS MODEL PEMBELAJARAN PJBL DI SEKOLAH DASAR - Dewi, Santi Kurnia; Ekawati, Ratna; Dewi, Radeni Sukma Indra (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to test the effectiveness of the Project-Based Learning (PjBL) model in elementary schools through a literature review. Using the Systematic Literature Review method, data were collected from relevant research journals published between 2023 and 2024. The data analysis technique used was the systematic review method. The analysis of ten journals indicates that the implementation of the PjBL model has a positive impact on improving student learning outcomes, including enhancement in critical thinking, creativity, collaborative thinking skills, and communication. The PjBL learning model has proven effective in various subjects such as Mathematics, Science, and Art, as evidenced by a significant increase in the average scores of students after the implementation of PjBL. Additionally, PjBL encourages active student participation in the learning process through tasks and real-life projects that are relevant to daily life. However, its effectiveness is highly dependent on the teacher's competence in designing and managing the learning process. This study concludes that PjBL is an effective learning model for improving student learning outcomes and 21st-century skills in elementary schools, with the caveat that continuous evaluation is necessary to optimize its implementation.